2016
DOI: 10.1002/star.201600194
|View full text |Cite
|
Sign up to set email alerts
|

The roles of starch metabolic pathways in the cold‐induced sweetening process in potatoes

Abstract: Cold-induced sweetening (CIS) is critical for the postharvest quality of potato tubers, and the accumulation of reducing sugar is regulated by several metabolic pathways, such as starch synthesis and degradation, hexogenesis, glycolysis, and anaerobic respiration. Starch is the energy source of storage organs, and its metabolism plays an important role in potato CIS. Here, the processes of starch synthesis and degradation in potato tubers and the functions of related genes in potato CIS are summarized, e.g., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 109 publications
(126 reference statements)
1
15
0
1
Order By: Relevance
“…Furthermore, studies have revealed that in addition to the VINV pathway, sucrose is also broken down to UDP-glucose and fructose via the sucrose synthase (SuSy) pathway 13,21 (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, studies have revealed that in addition to the VINV pathway, sucrose is also broken down to UDP-glucose and fructose via the sucrose synthase (SuSy) pathway 13,21 (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Sucrose levels increased with storage time for Verdi but decreased for the CIS-susceptible varieties. Conversion of sucrose to reducing sugars is known to occur simultaneously through two pathways: the VINV pathway and the sucrose synthase (SuSy) pathway 13,21 . The very low activity of the VINV pathway in Verdi forces sucrose to be broken down through the SuSy pathway to produce UDP-Glucose which is subsequently converted back to sucrose through a series of enzymatic reactions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Крахмалсинтаза, связанная с крахмальными гранула-ми (granule-bound starch synthase), ответственна за синтез амилозы, тогда как растворимые крахмалсинтазы I-III от-вечают за синтез амилопектина. Ветвление амилопектина осуществляет ветвящий фермент SBE (starch-branching enzyme, EC 2.4.1.18), который отщепляет от неразветвлен-ной цепочки фрагмент и переносит его к шестому атому углерода глюкозы (Zhang et al, 2017). Путь биосинтеза крахмала описан во многих источниках, в то время как регуляция этого процесса до сих пор остается малоизу-ченной (Van Harsselaar et al, 2017).…”
Section: ассоциативная семантическая сеть молекулярно-генетической реunclassified